Detection of meteorological influence on bread wheat quality in Hebei province, China based on the gradient boosting decision tree - Zhang, Xinyue; Chen, Keyao; Li, Kuo (Frontiers in Plant Science, 2023)
Wheat grain quality is equivalent to grain yield in terms of ensuring food security under climate change but has received less attention. Identifying critical meteorological conditions in key phenological periods to account for the variability in grain protein content (GPC) can provide insight into linkages between climate change and wheat quality. The wheat GPC data from different counties of Hebei Province, China during 2006-2018 and corresponding observational meteorological data were used in our study. Through a fitted gradient boosting decision tree model, latitude of the study area, accumulated sunlight hours during the growth season, accumulated temperature and averaged relative humidity from filling to maturity were suggested as the most relevant influencing variables. The relationship between GPC and latitude was distinguished between areas north and south of 38.0° N. GPC decreased with the increasing latitude in areas south of 38.0° N, where at least accumulated temperatures of 515 °C from filling to maturity were preferred to maintain high GPC. Besides, averaged relative humidity during the same phenological period exceeding 59% could generate an extra benefit to GPC here. However, GPC increased with increasing latitude in areas north of 38.0° N and was mainly attributed to more than 1500 sunlight hours during the growth season. Our findings that different meteorological factors played a major role in deciding regional wheat quality provided a scientific basis for adopting better regional planning and developing adaptive strategies to minimize climate impacts.